2021
DOI: 10.1186/s13102-021-00248-6
|View full text |Cite
|
Sign up to set email alerts
|

Does kinesiotaping can improve static stability of the knee after anterior cruciate ligament rupture? A randomized single-blind, placebo‐controlled trial

Abstract: Background The aim of the study was the assessment of the early impact of the selected kinesiotaping technique on the static stability of the knee joint in patients with ACL rupture on the basis of stabilographic parameters. Methods Sixty-two patients with a complete ACL rupture (32 patients in experimental group and 30 patients in placebo group) took part in the randomized single-blind, placebo-controlled trial. The ligament technique of KT was ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(14 reference statements)
2
3
0
Order By: Relevance
“…However, in the YBT, significant differences were only found over time in the anterior displacement, but not between groups, which is in line with the results reported by Espí-López et al in healthy amateur soccer players [24]. Only in studies performed in individuals with a recent ACL rupture did KT improve the static stability [22,23]. This finding is clinically relevant because it may be associated with a potential reduction in the risk of ACL injury, since an enhanced knee valgus is a risk factor for this type of injury [26].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in the YBT, significant differences were only found over time in the anterior displacement, but not between groups, which is in line with the results reported by Espí-López et al in healthy amateur soccer players [24]. Only in studies performed in individuals with a recent ACL rupture did KT improve the static stability [22,23]. This finding is clinically relevant because it may be associated with a potential reduction in the risk of ACL injury, since an enhanced knee valgus is a risk factor for this type of injury [26].…”
Section: Discussionsupporting
confidence: 88%
“…In individuals with a recent ACL rupture, KT application at the knee has been shown to improve proprioception, strength, and static balance [21][22][23]. However, in healthy young athletes, there are inconclusive results about the effectiveness of KT at the knee.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with short-term KT application (1-3 hours) for individuals with ACL rupture (27,32), we observed improved balance. It is well established that proprioception and muscle strength influence single-leg stance (24).…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, to our knowledge, there is no information regarding its long-term use in the presence of an ACL rupture. There is evidence of improved perceived functions of the affected knee joint (5,27), gait pattern (5), balance (27,32), and enhanced proprioception (5,27) after short-term application of KT (#3 hours) in individuals with surgically untreated ACL ruptures. In addition, there is evidence of improved muscle strength (after 10 days of KT application after ACL reconstruction) (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the positive effects of application of kinesiology tape (KT) on the skin might be explained by increased activation of mechanoreceptors and increased interstitial space [10]. Previous studies established that short-term (1-3 h) application of KT improved postural control, single-hop distance, gait pattern, proprioception, and subjectively perceived functions of the affected knee in individuals with surgically untreated ACL tear [11][12][13]. Furthermore, there is evidence that 4-week application of KT improves muscular strength.…”
Section: Introductionmentioning
confidence: 99%